Changing Care Settings for Injuries. (December 2022) - Buttorff, Christine; Heins, Sara E.; Al-Ibrahim, Hamad
Tracking injury rates is important for surveillance purposes but little data exist for injuries outside of emergency department visits. We assess the share and type of injuries reported in urgent care centers (UCCs) compared with other settings. We used FAIR Health claims data from 2016 through the first quarter of 2019 to calculate the percent of claims and most common types of injuries. Of the 197 million injury claims, 62% occurred in office settings and 17% in hospital outpatient departments (HOPDs), 5% in inpatient and in ED settings, and less than 2% in UCCs. Injury claims in UCCs increased 6% from 2016 to 2018, whereas injury claims in EDs declined 24%. Overall, physician offices and HOPDs accounted for the largest share of injury care, but UCCs represented the fastest growing setting to treat injuries.